2016
DOI: 10.1002/jcla.22058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Microalbuminuria and Urine Ischemia‐Modified Albumin Levels in Patients with Diabetic Nephropathy

Abstract: Introduction: Ischemia-modified albumin (IMA) is a marker which can be associated with oxidative stress in various ischemic and non-ischemic processes. Oxidative stress plays roles in diabetes mellitus, its complications and pathogenesis. Serum IMA levels are examined in various clinical events. However, urine IMA levels have not yet been evaluated in diabetic patients. In this study, we aim to examine the relationship between metabolic features and urine microalbuminuria levels of diabetic patients and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Statistically significant positive correlations were observed between IMA and creatinine and between IMA and MA. Similar results were reported by Dahiya et al, whereas contrasting results were reported by Bilgi et al who reported no correlation between IMA levels and albuminuria and creatinine (26,27). Based on the association between IMA and the parameters used in the routine diagnosis of renal dysfunction, our results suggest that IMA is a useful marker for detecting early renal dysfunction in DN.…”
Section: Discussionsupporting
confidence: 89%
“…Statistically significant positive correlations were observed between IMA and creatinine and between IMA and MA. Similar results were reported by Dahiya et al, whereas contrasting results were reported by Bilgi et al who reported no correlation between IMA levels and albuminuria and creatinine (26,27). Based on the association between IMA and the parameters used in the routine diagnosis of renal dysfunction, our results suggest that IMA is a useful marker for detecting early renal dysfunction in DN.…”
Section: Discussionsupporting
confidence: 89%
“…[10][11][12] The presence of MAU in Type-2 DM is considered a potential risk for developing progressive renal diseases as well as proving as a diagnostic marker of predilection for generalized cardiovascular disease. 13,14 In our study, 23.8% of treatment naive Type-II diabetic patients had MAU. The 44 patients (19.4%) had silent myocardial infarction.…”
Section: Discussionmentioning
confidence: 50%
“…10-13 Our findings are not consistent with Bilgi et al who could not find any association of microalbuminuria of diabetic nephropathy and CVD. 14 In another study, by Yurtdas et al, it was found that there was a significant inverse association between MAU, and Silent MI in treatment naive Type-II DM patients and even in non diabetic patients. 15,16 Limitation of the study: The current study is its small sample size and population selection from a tertiary care hospital, which is not representative of our total population.…”
Section: Discussionmentioning
confidence: 92%
“…[13] The process starts from the early stages of diabetic nephropathy to ESRD, cardiovascular diseases also progressively develop in these patients and cardiovascular diseases (CVDs) are the most important reason of the mortality in DN patients. [15] Use of the ACR in urine samples is recommended as the preferred screening strategy for albuminuria in diagnosis of diabetic nephropathy in diabetic patients. [15,16] Relation of increased urine ACR with Apo B containing lipoproteins has also been proved previously.…”
Section: Association Of Albumin To Creatinine Ratio With Cardiovasculmentioning
confidence: 99%
“…[15] Use of the ACR in urine samples is recommended as the preferred screening strategy for albuminuria in diagnosis of diabetic nephropathy in diabetic patients. [15,16] Relation of increased urine ACR with Apo B containing lipoproteins has also been proved previously. [8] The present study attempted to find out the association of ACR with biochemical and cardiovascular markers in diabetic nephropathy patients.…”
Section: Association Of Albumin To Creatinine Ratio With Cardiovasculmentioning
confidence: 99%